Henoch-Schönlein Purpura With Intussusception: A Case Report - Hui-Chien Lai (Elsevier, 2010)
Gastrointestinal symptoms in Henoch-Schönlein purpura (HSP) are common and occur in about two-thirds of HSP patients. Surgical intervention is only required in a minority of cases. Intussusception is a rare complication and the most common surgical indication for HSP. We report a 3-year-old boy with HSP and clinical manifestations of palpable skin rash lasting for 4 days, fever for 3 days, intermittent abdominal cramping pain, and left ankle arthralgia lasting for several hours. Abdominal sonography revealed characteristic signs of intussusception including a doughnut sign and a pseudo-kidney sign in the right upper quadrant of the abdomen. After unsuccessful initial reduction by air enema, surgical reduction was arranged and manual reduction of the ileocecal intussusception without bowel resection was carried out.